Implementasi Penerbitan Healthbook TB. Pacific Star II pada Karantina Dumai oleh PT. Berlian Ocean Shipping - Sabila, Fadiyah Hani; Gultom, Dika Praza (Politeknik Bumi Akpelni Semarang, 2026)
The issuance of a Health Book (Ship's Health Book) is a crucial component of the health quarantine monitoring system at international ports to prevent the spread of infectious diseases across borders. This study aims to analyze the implementation of Health Book issuance procedures for the vessel TB. Pacific Star II, managed by PT. Berlian Ocean Shipping within the operational area of the Class I Health Quarantine Office in Dumai. The research method used is descriptive qualitative, with data collection techniques through participatory observation during field practice, interviews, and documentation studies. The results indicate that the issuance process involves a series of physical ship inspections, crew document validation, and the use of the digital feature